2008
DOI: 10.1556/oh.2008.28327
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical alterations in patients with Down syndrome

Abstract: The lower homocysteine, folic acid and B 12 values may be considered as the consequence of an increased cystathionine-beta-synthase activity ("atheroma free model"). There was no significant alteration in antioxidant activity level. It can be supposed that the hydrogene peroxide produced due to increased expression of superoxide dismutase is metabolized by the induced glutathione-peroxidase and catalase keeping by this the balance of the antioxidant system. This hypothesis is supported by the normal N-acetyl-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
3
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
5
3
1
Order By: Relevance
“…A correlation between protein level and substrate concentration was established in both Ms and Ts males versus control animals and confirmed the parallel, for Cbs , between gene expression level and protein level. Interestingly, the homocysteine level in Ts females was not affected in our study a result similar to some obtained in human T21 patients at the adult stage (80,81) but controversial to others obtained in younger individuals (37). …”
Section: Discussionsupporting
confidence: 84%
“…A correlation between protein level and substrate concentration was established in both Ms and Ts males versus control animals and confirmed the parallel, for Cbs , between gene expression level and protein level. Interestingly, the homocysteine level in Ts females was not affected in our study a result similar to some obtained in human T21 patients at the adult stage (80,81) but controversial to others obtained in younger individuals (37). …”
Section: Discussionsupporting
confidence: 84%
“…Reynolds (35) found that antioxidant supplementation did not improve the development of children with DS. Interestingly, a study assessing total serum antioxidant activity levels, but in contrast to previous reports, has found no significant difference between control individuals and those with DS (36) . However, increased serum concentrations of lipid peroxidation products, i.e.…”
Section: Discussioncontrasting
confidence: 71%
“…Formimidoyltransferase cyclodeaminase (FTCD) is another gene located on the long arm of chromosome 21 which provides instruction to produce formimimotransferase cyclodeaminase enzyme involved in the metabolism of histidine and the production of folate required for synthesis of purine, pyrimidines and amino acids. Variations in the activities of various enzymes and plasma electrolyte concentrations to differ from normal parameters in DS have previously been reported especially in HSA 21 associated proteins such as S100B [7]. The levels of S100B protein were 4-8 times higher in DS individuals compared to the reference values.…”
Section: Gene-dosage Effectsmentioning
confidence: 83%